PENGEMBANGAN ELEKTRONIK MODUL INTERAKTIF MENGGUNAKAN FLIP PDF PROFESSIONAL MATERI SIKLUS HIDROLOGI - Delima Nur Aulia; Santa; Suci Siti Lathifah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Electronic research interactive modules using flip pdf professional hydrological cycle material was developed using the ADDIE R&D Model approach. In expert validation it was declared valid because it obtained the percentage of media experts by 93.8%, linguists by 98.4%, and material experts by 94%. Based on the readability test, it obtained a percentage of 97.5% with a very decent category. The average pretest, posttest, and n-gain scores were respectively 64.66, 86.33, and 0.6 (60%) which fall into the medium category with a fairly effective level of effectiveness. While the results of the teacher and student response questionnaire were 92% and 93.8%, respectively, in the very good category.